Analysis of welding Au nanowires into T junctions. Issue 12 (12th August 2016) - Wu, Cheng-Da; Fang, Te-Hua; Hsiao, Jhih-Wei
Abstract: The effects of temperature and size on the welding of Au nanowires (NWs) into T junctions is studied using molecular dynamics simulations based on the second-moment approximation of the many-body tight-binding potential. Simulation results show that when the top NW approaches the bottom one, it elongates towards the bottom one just before welding due to the interaction of the van der Waals attractive force. During welding, the bottom NW gradually reaches critical bend deformation through successive pressure applied from the top one, followed by buckling of the top NW. The structural order of NWs significantly decreases with increasing welding temperature or decreasing NW width. Welding at high temperatures (700 K or above) causes alignment difficulty due to an unstable NW geometry or even welding failure due to a decrease in NW length. Smaller NWs have larger stress during the welding process.